2014
DOI: 10.1016/j.ajo.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus in Childhood Eyelid Ptosis

Abstract: Purpose To report the prevalence and causes of strabismus among children with eyelid ptosis diagnosed in a well-defined population over a 40-year period. Design Retrospective, population-based cohort study. Methods We retrospectively reviewed the charts of one hundred and seven patients (< 19 years) for the prevalence and causes of strabismus who were diagnosed with childhood eyelid ptosis as residents of Olmsted County, Minnesota, from January 1, 1965, through December 31, 2004. Results Strabismus was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Both blepharoptosis and conjunctival prolapse interfere with the pupillary axis, resulting in deprivation amblyopia in children under seven years of age [9]. Especially, physicians must consider this complication in all children under two years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both blepharoptosis and conjunctival prolapse interfere with the pupillary axis, resulting in deprivation amblyopia in children under seven years of age [9]. Especially, physicians must consider this complication in all children under two years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of strabismus in simple congenital ptosis is approximately 9.9% and is higher compared to its incidence in the general population (1% to 5%) [9]. It is suggested that strabismus results from visual occlusion and disruption of binocularity by the ptotic eyelid [9]. Therefore, careful examinations are essential in patients presenting with ptosis after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Familial inheritance patterns of NSCP include autosomal dominant inheritance, autosomal recessive inheritance, and X-linked dominant inheritance. Generally, but not in all cases, patients may have strabismus and eyestrain may be secondary to visual occlusion and disruption by the ptotic eyelid [13]. Other ocular symptoms include astigmatism due to eyelid tension and changes in the corneal curvature [14], amblyopia due to astigmatic anisometropia or deprivation [1], and headaches due to forced brow elevation to increase the visual field.…”
Section: Introductionmentioning
confidence: 99%